29.5k views
1 vote
PLEASE HELP ME NOW URGENT

PLEASE HELP ME NOW URGENT-example-1

2 Answers

6 votes

3±√21. The equation
y^(2)-6y-12=0 has two possible solutions 3+√21 y 3-√21.

If we have a general quadratic equation
ay^(2) +by+c=0 we can solves the equation by completing the square. First, we divide the quadratic equation by a, we obtain
y^(2) +(b)/(a) y+(c)/(a) =0.

For this problem, we have
y^(2)-6y-12=0

We can skipped division in this example since the coefficient of
x^(2) is 1.

Move the term c to the right side of the equation


y^(2)-6y=12

Completing the square on the left side of the equation and balance this by adding the same number to the right side of the equation, with b = -6.


((b)/(2))^(2) =((-6)/(2))^(2)=(-3)^(2) =9


y^(2)-6y+9=12+9


(y-3)^(2)=21

Take the square root on both sides of the equation:

y - 3 = ±√21

Add 3 from both sides:

y = 3 ± √21

User UmYeah
by
6.0k points
0 votes

ANSWER


y = 3 \pm √(21)

Step-by-step explanation

The quadratic equation is:


{y}^(2) - 6y - 12 = 0

Group variable terms:


{y}^(2) - 6y = 12

Add the square of half, the coefficient of y to both sides.


{y}^(2) - 6y + ( - 3) ^(2) = 12 + ( - 3) ^(2)


{y}^(2) - 6y + 9= 12 + 9

The LHS us now a perfect square trinomial:


{(y - 3)}^(2)= 21

Take square root:


y - 3 = \pm √(21)


y = 3 \pm √(21)

The first choice is correct.